How Do Early Screening Interventions For Frailty Impact The Prevention Of Delirium In Older Adult Patients? - Calista Giovani; Yudhi Hajianto Nugroho; Mutia Juliana (The International Journal of Medical Science and Health Research, 2025)
Introduction: Frailty and delirium are common and interrelated conditions affecting older adults, especially those undergoing hospitalization or surgery. Early screening for frailty has been proposed as a strategy to identify vulnerable patients and implement preventive measures to reduce the incidence of delirium. Methods: This review analyzed interventional studies published within the last decade that assessed the impact of early frailty screening combined with individualized care plans on delirium prevention in older adults. Studies included randomized controlled trials, quasi-experimental designs, and prospective interventions involving patients aged 65 years or older across various healthcare settings. Frailty screening tools and delirium assessment methods were evaluated alongside intervention timing and types. Results: Multiple studies demonstrated significant reductions in delirium incidence following early frailty screening and targeted interventions. For example, delirium rates decreased from 10.0% to 3.3% in vascular surgery patients after geriatric comanagement, and from 29.2% to 11.3% in colorectal surgery patients receiving comprehensive geriatric assessment. Interventions ranged from preoperative cognitive exercises and multimodal prehabilitation to in-hospital multidisciplinary care models. Some studies reported improved functional and cognitive outcomes, while a few noted no significant changes in longer-term results. Discussion: Early frailty screening enables proactive identification of at-risk older adults, facilitating the delivery of personalized, multidisciplinary interventions that effectively reduce delirium incidence. The timing of intervention—particularly preoperative assessments—plays a crucial role in optimizing outcomes. Multidisciplinary collaboration and individualized care plans are common success factors. However, challenges such as patient non-compliance, small sample sizes, and external factors like the COVID-19 pandemic may limit effectiveness in some contexts. Conclusion: Early screening for frailty combined with tailored, multidisciplinary care is an effective approach to delirium prevention in older adults. Continued research is needed to refine screening tools, intervention protocols, and implementation strategies to enhance patient outcomes and broaden applicability across healthcare settings.